A simple high-intensity UV-photon source for photochemical studies in UHV: Application to the photoconversion of norbornadiene to quadricyclane - Schwarz, Matthias; Schuschke, Christian; Nascimento Silva, Thais; Mohr, Susanne; Waidhas, Fabian; Brummel, Olaf; Libuda, Jörg (Review of Scientific Instruments, 2019)
Photochemical in situ studies in a well-controlled surface science environment can help to understand photochemical reactions in organic thin films in more detail. To perform such studies without external focusing or light guiding systems, we designed a high-intensity UV-photon source, which is compatible with an ultra-high vacuum (UHV) environment. The UV source is based on a high power light-emitting diode (LED), soldered onto a copper heat reservoir to avoid overheating. The LED can be placed in close vicinity in front of a single crystal, providing flux densities of 2 x 10(18) photons s(-1) cm(-2) at a wavelength of 365 nm. Thus, the device provides light intensities one order of magnitude higher as compared to conventional continuous wave arc lamps, at only a small variation of the flux of less than +/- 20% over a sample surface of 10 x 8 mm(2). The UV source is mounted in a UHV infrared reflection absorption spectroscopy system and triggered by using the IR spectrometer. This allows fully automatized in situ IR studies of photochemical reactions at interfaces and thin films. We prove the functionality of the device by studying the photochemical conversion of norbornadiene (NBD) to quadricyclane (QC) mediated by the photosensitizer 4,4'-bis(dimethylamino) benzophenone (Michler's ketone, MK). NBD and MK were grown by physical vapor deposition in the form of thin films on Pt(111) at 120 K. Even at prolonged UV irradiation (>100 s), the temperature of the sample increased by less than 10 K. We report first successful conversion of NBD to QC under UHV conditions and follow the conversion behavior as a function of the photon dose and NBD/MK ratio. Initial quantum yields of up to 23% and selectivity for a QC of 70% are obtained at NBD/MK of 7.4:1, indicating good electronic coupling between NBD and MK even in a frozen multilayer. For both very small and very large NBD loadings, the conversion efficiency decreases, which is attributed to the effect of the metallic substrate and phase separation in thick multilayers, respectively. Published under license by AIP Publishing.
CRIS-Team WoS Importer:2019-03-20

Dehydrogenation of the Liquid Organic Hydrogen Carrier System Indole/Indoline/Octahydroindole on Pt(111) - Bachmann, Philipp; Schwarz, Matthias; Steinhauer, Johann; Späth, Florian; Düll, Fabian; Bauer, Udo; Nascimento Silva, Thais; Mohr, Susanne; Hohner, Chantal; Scheuermeyer, Marlene; Wasserscheid, Peter; Libuda, Jörg; et al. (Journal of Physical Chemistry C, 2018)
Indole derivatives are considered as promising liquid organic hydrogen carriers for renewable energy storage. Using X-ray photoelectron spectroscopy, temperature-programmed desorption, and infrared reflection absorption spectroscopy, we investigated low-temperature adsorption and dehydrogenation during heating of indole, indoline, and octahydroindole on Pt(111). For all three molecules, we find deprotonation of the NH bond above 270 K, accompanied with dehydrogenation of indoline and octahydroindole via an indole intermediate, resulting in an indolide species above 300 K. For octahydroindole, we also find a side reaction yielding small amounts of a pi-allyl species between 170 and 450 K. Above 450 K, decomposition of the remaining indolide species takes place.

Model Catalytic Studies of Novel Liquid Organic Hydrogen Carriers: Indole, Indoline and Octahydroindole on Pt(111) - Schwarz, Matthias; Bachmann, Philipp; Nascimento Silva, Thais; Mohr, Susanne; Scheuermeyer, Marlene; Späth, Florian; Bauer, Udo; Düll, Fabian; Steinhauer, Johann; Hohner, Chantal; Döpper, Tibor; Noei, Heshmat; et al. (Chemistry - A European Journal, 2017)
Indole derivatives were recently proposed as potential liquid organic hydrogen carriers (LOHC) for storage of renewable energies. In this work, we have investigated the adsorption, dehydrogenation and degradation mechanisms in the indole/indoline/octahydroindole system on Pt(111). We have combined infrared reflection absorption spectroscopy (IRAS), X-ray photoelectron spectroscopy (XPS) and DFT calculations. Indole multilayers show a crystallization transition at 200 K, in which the molecules adopt a strongly tilted orientation, before the multilayer desorbs at 220 K. For indoline, a less pronounced restructuring transition occurs at 150 K and multilayer desorption is observed at 200 K. Octahydroindole multilayers desorb already at 185 K, without any indication for restructuring. Adsorbed monolayers of all three compounds are stable up to room temperature and undergo deprotonation at the NH bond above 300 K. For indoline, the reaction is followed by partial dehydrogenation at the 5-membered ring, leading to the formation of a flat-lying di-sigma-indolide in the temperature range from 330-390 K. Noteworthy, the same surface intermediate is formed from indole. In contrast, the reaction of octahydroindole with Pt(111) leads to the formation of a different intermediate, which originates from partial dehydrogenation of the 6-membered ring. Above 390 K, all three compounds again form the same strongly dehydrogenated and partially decomposed surface species.
Keywords: density functional theory; infrared reflection absorption spectroscopy; liquid organic hydrogen carrier; octahydroindole; X-ray photoelectron spectroscopy